A Beginner’s Guide to Economic Research and Presentation - Edwards, Jeffrey A (Business Expert Press, 2013)
Ebook from IG Library ; Unlike other books which take a descriptive approach to the subject, the book employees a step-by-step approach to the teaching of how to conduct, write up and present economics research. Conducting good research is critical to any student of economics. Writing good research papers is equally important--yet many students have not been given the proper tools to convey cogently the results of their research. A Beginner's Guide to Economic Research and Presentation is intended to address and redress this need. This book is literally a step-by-step approach to the first-time writing of an undergraduate or MBA level research paper in the field of economics. The primary audience for this book is those students who have conducted research or written a research paper. In particular, Writing Research for Economics addresses would-be researchers in the field of economics. Such an audience might include undergraduate business majors (especially those students majoring or minoring in economics) MBA and graduate students in economics. Most books concerned with research writing are broadly applied. They approach the subject generally, which is to say that they don't lay out a particular path to conducting research. Yet a specific path offering a specific focus to writing research is exactly what is needed for most students. This book provides that focus. Whereas other books provide an overview of how to present research, with only cursory suggestions and tips, A Beginner's Guide to Writing and Presenting Economics Research provides precise details on all aspects of research writing, including how many Power Point slides one should prepare for presentations and how much content should be on each slide. In short, unlike other books, this book provides a specific approach to conducting research, writing a paper, and presenting its material.